Direct comparison of 129Xe diffusion measurements with quantitative histology in human lungs. Issue 1 (17th January 2016) - Thomen, Robert P.; Quirk, James D.; Roach, David; Egan‐Rojas, Tiffany; Ruppert, Kai; Yusen, Roger D.; Altes, Talissa A.; Yablonskiy, Dmitriy A.; Woods, Jason C.
Abstract : Purpose: Chronic obstructive pulmonary disease (COPD) is an irreversible lung disease characterized by small‐airway obstruction and alveolar‐airspace destruction. Hyperpolarized 129 Xe diffusion MRI of lung is a promising biomarker for assessing airspace enlargement, but has yet to be validated by direct comparison to lung histology. Here we have compared diffusion measurements of hyperpolarized (HP) 129 Xe in explanted lungs to regionally matched morphological measures of airspace size. Methods: Explanted lungs from five COPD patients and two idiopathic pulmonary fibrosis (IPF) patients were imaged using MRI with hyperpolarized 129 Xe using a two‐b‐value gradient‐echo diffusion sequence, and 34 histological samples were taken from these lungs for quantitative histology. Mean‐linear‐intercept (Lm ) was compared with spatially matched measures of apparent diffusion coefficient (ADC) from 129 Xe MRI. Results: The mean ADC from COPD lung samples was 0.071 ± 0.011 cm 2 /s, and for IPF lungs was 0.033 ± 0.001 cm 2 /s ( P  < 10 −15 between groups). The mean Lm in COPD samples was 0.076 ± 0.027 cm and 0.041 ± 0.004 cm in IPF ( P  = 2.7 × 10 −7 between groups). The Pearson‐correlation between ADC and Lm measurements was r  = 0.59. Conclusions: Diffusion MRI of HP 129 Xe quantifies regional airspace enlargement in COPD. 129 Xe ADC showed much less overlap between groups than quantitative histology, consistent with our past experience with 3 He diffusion MRI in COPD. Magn Reson Med 77:265–272, 2017. © 2016 Wiley Periodicals, Inc.